The ears of butterflyfishes (Chaetodontidae): 'Hearing generalists' on noisy coral reefs? - Webb, J.; Herman, J.; Woods, C.; Ketten, Darlene (Blackwell Publishing, 2010)
Analysis of the morphology of all three otolithic organs (sacculus, lagena and utriculus), including macula shape, hair cell morphology, density, orientation pattern, otolith morphology and the spatial relationships of the swimbladder and ear, reveals that butterflyfishes in the genera Chaetodon (which has anterior swimbladder horns) and Forcipiger (which lacks anterior swimbladder horns) both demonstrate the ear morphology typical of teleosts that lack otophysic connections, fishes that have traditionally been considered to be 'hearing generalists'.